Lévy-stable autoregressive model for the federal funds rate - Nacera Helal, Tawfiq Fawzi Mami, Hakim Ouadjed (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we will try to adjust the behaviour of the US Federal Funds interest rate to a model of autoregressive Levy-stable. We will conduct a series of tests after which it will offer the best model for this data series distributed in time, in this case, a linear model type AR (1) stationary whose distribution i.i.d. innovations would be a stable Lévy law and proceed thereafter to the estimation of nine parameters for this model